Nine Model Programs for Young Children Program Summaries for Potential Implementation. Volume I - Quillian, Benjamin F., Jr.; Rogers, Kathryn S.; National Coordination Center for Early Childhood Education, St. Ann, MO. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
This survey, representing a wide spectrum of teaching strategies and educational outlooks, is the result of a number of requests to the National Program on Early Childhood Education (NPECE) for a concise description of a variety of tested programs for young children that can be installed by local communities. A requirement of these programs was that they be well-defined, easily transportable, reasonably economical, and consistent in attaining positive educational outcomes. Also important were availability of training and support services. The programs considered were for 4- to 6-year-olds. Target audiences were bilingual, disadvantaged, and preschool or early elementary children. The four teaching strategies represented are open classroom, structured classroom, individualized instruction, and non-institutionalized instruction. Specific program descriptions under each strategy are: open classroom, the Tucson Early Education Model (TEEM), and the Education Development Center Approach (EDC); bilingual education, the Bilingual Early Childhood Program (SEDL) and the Oral Language Program (SWCEL); structured classroom, the Demonstration and Research Center for Early Education (DARCEE)/ National Program on Early Childhood Education (NPECE) Program, and the Behavior Analysis Plan; individualized instruction, the Responsive Model Program and the Primary Education Project (PEP); and non-institutional instruction, the Florida Parent Education Model. (MS)
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
ERIC Note: For Volume II, see PS 008 722.
Educational level discussed: Early Childhood Education.
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavior Change; Bilingual Education; Bilingual Students; Disadvantaged Youth; Early Childhood Education; English (Second Language); Home Visits; Individualized Instruction; Intervention; Open Education; Parent Participation; Preschool Children; Preschool Curriculum; Preschool Education; Program Descriptions; Program Evaluation; Spanish Speaking; Teaching Methods; Traditional Schools; Bilingual Early Childhood Program -- Demonstration and Research Ctr Early Child Educ -- Education Development Center MA -- Florida Parent Education Model -- Oral Language Program -- Primary Education Project -- Project Follow Through -- Responsive Model Program -- Tucson Early Education Model; Reports, Descriptive